Effect of Arbutus pavarii, Salvia officinalis and Zizyphus Vulgaris on growth performance and intestinal bacterial count of broiler chickens - A.A. Asheg; S.M. EL-Nyhom; K.M. Ben Naser; A.H. Kanoun; Y.M. abouzeed (International Journal of Veterinary Science and Medicine, 2014)
A study was conducted to determine the effect of three native plants from El-Jabal al ELAkhdar, (Libya) on performance and cecal coliform count of broiler chickens. A total of 1260 one-day-old male Cobb chickens were used in the experiment. The birds were assigned to 7 treatment groups (6 replicates per treatment). The dietary treatments included basal diet with no additive (control), and 6 other dietary treatments (Arbutus pavarii, Salvia officinalis and Zizyphus Vulgaris) each of which was added at the rate of 0.5 g and 1 g/kg of basal diet. Results explicitly revealed that all dietary treatments had a significant effect on body performance of broiler chickens compared to the control with the exception of the dietary treatment of S. officinalis at dosage of 0.5 g/kg that has expressed noticeable reduction in body weight. Coliform counts in the cecum of birds receiving 1% A. pavarii and 1% Z. Vulgaris were significantly lower (P ⩽ 0.05) than those of control group from early weeks of treatments, whereas all plant shows a significant lowering (P ⩽ 0.05) of cecal coliform count during the rest of experiment compared to control group. These results emphasize the potential biotic role of such plants together with the immune modulating effects on treated birds. However, further pharmacological and clinical work should be adopted in the future to present an obvious understandable theory behind the potential beneficial as well as side effects of such natural plants.